(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of social media use and analyze the association between the level of social media use and sleep quality among nursing students at Pham Ngoc Thach University of Medicine. Subjects and methods: A cross-sectional descriptive study was conducted on 460 nursing students from first to fourth year at Pham Ngoc Thach University of Medicine between July 2025 and July 2026. Data were collected using self-administered questionnaires, including the BSMAS and the PSQI. Statistical analyses were performed using appropriate tests with a significance level of p < 0.05. Results: Among 460 nursing students, 81.3% had poor sleep quality, with a mean PSQI score of 7.46 ± 2.38. Unhealthy behaviors such as staying up late and using electronic devices before bedtime were common and associated with impaired daytime functioning. Male students had a significantly higher risk of poor sleep quality than females (OR = 2.90; p = 0.006), while academic and economic factors showed no significant association (p > 0.05). In multivariable logistic regression, social media use behaviors, including prolonged use (> 3 hours/day), nighttime use, and entertainment purposes (especially video viewing) - increased the risk of poor sleep quality by 2.1-2.6 times (p < 0.01). Additionally, stress and lifestyle disturbances were strongly associated with poor sleep quality, whereas general phone use was not statistically significant. Conclusion: Poor sleep quality among nursing students is prevalent and mainly associated with behavioral and